Вивчення реологічних властивостей м’якої лікарської форми празіквантелу для зовнішнього застосування - Романіна, Дар'я Михайлівна; Гладишев, Віталій Валентинович; Бурлака, Богдан Сергійович; Romanina, D. M.; Gladishev, V. V.; Burlaka, B. S. (My University, 2016)
Структурно-механічні характеристики мають помітний вплив на процеси вивільнення і всмоктування лікарських речовин із мазей, а також на їх споживчі властивості: намазуваність, адгезію, здатність видавлюватися з туб [1, 2, 3]. Зручність і легкість нанесення мазі асоціюється у пацієнта з тими зусиллями, які він докладає для розподілу на поверхні шкіри певної кількості мазі. Цей процес є аналогічним тому, який відбувається під час зсуву в’язко-пластичного матеріалу в ротаційному віскозиметрі, а зусилля, що витрачається пацієнтом, є не що інше, як напруга зсуву, яка характеризує опірність матеріалу зсувним деформаціям за певної швидкості і може бути виміряна інструментально [4]. У зв’язку з цим, оцінка реологічних характеристик є важливим і невід’ємним фрагментом досліджень по створенню м’яких лікарських форм для дерматологічної практики [5, 6]. Кафедрою технології ліків Запорізького державного медичного університету в результаті комплексних фізико-хімічних, фармакотехнологічних і мікробіологічних досліджень науково обґрунтовано раціональний склад м’якої лікарської форми – мазі (крему) із празіквантелом для місцевої етіотропної фармакотерапії акнеподібніх дерматозів [7, 8]. Structural-mechanical characteristics exert a significant influence on the processes of the medications releasing, absorption in ointments and their consumer properties: spreadability, adhesion, extrudability from the tubes. In this connection evaluation of the rheologic properties is an important and inevitable fragment of the investigations in the realm of making of the semisolid dosage forms for the dermatologic practice. Efficient composition of the semisolid dosage form – ointment (cream) with praziquantel for the topical etiotropic pharmacotherapy of the acne similar dermatosis was developed on the department of technology of medication in Zaporozhye State Medical University as a result of the complex physico-chemical, pharmacotechnological and microbiological investigations. The aim of this work is study of consistent properties of the de veloped ointment composition. Study of structural-mechanical characteristics of the composition was carried out by the rotary viscosimeter Reotest-2 with cylindrical arrangement. As a result of the experiment it was established that consistent properties of the cream for external use with praziquantel 3% are practically thoroughly situated within rheologic optimum of consistence limits. Mechanical stability (1,19) describes composition as an exceptionally thixotropic system which provides with restorability after applying tension and allows to predict stability of consistent properties during a long-term storage. Calculated factors of dynamical flowing of the praziquantel topical dosage form on the emulsion base (Кd1 = 41,82%; Kd2 = 67,22%) quantitatively confirm satisfactory spreading degree of the system during application on the mucous membranes or in manufacturing process . Insignificant divergence of rheologic characteristics of the cream with praziquantel 3% for external use and its base indicates a deficiency of interactions between acti ve substance and excipients.
Study of the rheological characteris tics of the praziquantel semis olid dosage form for external use
Keywords: празіквантел; мазь; тиксотропність; механічна стабільність; praziquantel; ointment; thixotropy; mechanical stability